Bifurcated Temperature Profiles and the H-mode - Bishop, Christopher (Nuclear Fusion, 1986)
One of the most striking features of the H-mode, in contrast to the L-mode, is the existence of very steep pressure gradients in a narrow layer just inside the plasma boundary. In this paper, it is shown how the existence of H- and L-regimes, together with their characteristic profiles, is a natural consequence of the modified ballooning stability properties near a magnetic separatrix.